2012
DOI: 10.1007/s10654-012-9678-6
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of body mass index in pre-adolescence, young adulthood and late adulthood

Abstract: Increased body mass index (BMI) is a worldwide health issue. Individual differences in the susceptibility to increased BMI could be related to genes or environment. We performed a systematic review of genetic studies on BMI in pre-adolescence, young adulthood and late adulthood. We searched PubMed and EMBASE with heritability, body mass index, BMI, weight, height, anthropometry and twins as search terms. Studies reporting intra-pair correlations of healthy twin pairs that were raised together were included. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 49 publications
5
58
0
1
Order By: Relevance
“…In addition, specific genes which relate to UA, particularly genes e.g., SLC2A9, ABCG2, SLC22A12, and MAF, which encode for proteins involved in renal urate excretion, have been reported as being associated with genetic susceptibility to hyperuricemia [12,13]. Additionally, a systematic review of genetic studies on BMI has reported a strong genetic influence, and a genome-wide association study in Japan identified two novel BMI-associated loci e.g., CDKAL1 and KLF9 [14,15]. However, the association between UA and BMI may be confounded by genetic factors, since the previous epidemiological studies did not adjust for genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, specific genes which relate to UA, particularly genes e.g., SLC2A9, ABCG2, SLC22A12, and MAF, which encode for proteins involved in renal urate excretion, have been reported as being associated with genetic susceptibility to hyperuricemia [12,13]. Additionally, a systematic review of genetic studies on BMI has reported a strong genetic influence, and a genome-wide association study in Japan identified two novel BMI-associated loci e.g., CDKAL1 and KLF9 [14,15]. However, the association between UA and BMI may be confounded by genetic factors, since the previous epidemiological studies did not adjust for genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…This imbalance can be due to genetic or environmental risk factors, or more likely due to a combination of both, an intertwining of genetics and environment [3]. A general consensus is that about 65% of variation in obesity is genetic [4], and candidate genes include those that control energy expenditure and thermogenesis, such as those encoding mitochondrial uncoupling proteins (UCPs) [5].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests that obesity is about 65% genetic and that gene-environment interactions may confer an even greater susceptibility to obesity [30]. One leading hypotheses is that early environmental influences may induce epigenetic variation at specific loci that result in permanent defects in metabolism and increases in disease risk [31].…”
Section: Discussionmentioning
confidence: 99%